MO517: A Polygenic Risk Score for Reduced EGFR is Associated With Adverse Events in a Chronic Kidney Disease Cohort —the German Chronic Kidney Disease Study. (3rd May 2022) - Steinbrenner, Inga; Yu, Zhi; Jin, Jin; T. Schultheiß, Ulla; Kinga Kotsis, Fruzsina; Grams, Morgan; Coresh, Josef; Eckardt, Kai-Uwe; Sekula, Peggy; Chatterjee, Nilanjan; Köttgen, Anna
Abstract: BACKGROUND AND AIMS: Over 10% of the adult population worldwide is affected by chronic kidney disease (CKD). CKD is associated with an increased risk of kidney failure (KF), cardiovascular events and mortality. CKD is defined and staged by estimated glomerular filtration rate (eGFR), the most common measure of kidney function. Genome-wide association studies enable the calculation of polygenic risk scores (PRSs), e.g. for eGFR. The aim of this study was to investigate if a polygenic predisposition to lower eGFR is associated with KF, cardiovascular events and mortality in people with CKD, and if the eGFR PRS carries predictive ability. METHOD: A PRS for log(eGFR) was developed and tuned in independent, general population-based study samples consisting of European ancestry participants of the UK Biobank and the CKDGen Consortium via the LDpred algorithm [1]. Using genetic information and follow-up data of 4873 participants with moderate CKD enrolled in the German Chronic Kidney Disease study, we calculated, standardized and evaluated the association of the PRS with adverse endpoints. Main endpoints included KF, a composite endpoint of myocardial infarction, cerebral haemorrhage and stroke (3P-MACE), and overall mortality. Cox proportional hazard regression was conducted to estimate (cause-specific) hazard ratios (HRs). Predictive performance of the PRS for KF and 3P-MACE was assessed using prediction error curves and time-dependent c-index. The statistical significance level was Bonferroni-corrected for three main endpoints (P < .05/3). RESULTS: After a median follow-up time of 6.5 years, 619 patients died, 466 experienced KF, and 545 3P-MACE. Higher levels of the PRS, corresponding to a genetic predisposition to lower eGFR, were associated with higher risk for all three endpoints KF: HR 1.23, [95% confidence interval (95% CI) 1.12–1.35], 3MACE: 1.15 (1.06–1.25), mortality: 1.12 (1.04;1.22) after adjusting for baseline age, sex and two principal components. Across deciles of the eGFR PRS, participants in the highest decile, corresponding to the genetically lowest eGFR, had a >2-fold increased risk of KF compared with those in the lowest decile [HR = 2.13 (1.39–3.27), Fig. 1 ]. No distinct improvement in the prediction performance for KF was observed when adding the PRS to the well-established KF risk equation by Tangri et al. [2]. This also held true for the added predictive ability of the PRS for 3P-MACE when compared with a model with established cardiovascular risk factors. CONCLUSION: Our study revealed a significant association between a polygenic predisposition to lower eGFR and KF, cardiovascular events, and mortality among people with moderate CKD, emphasizing the importance of genetic background even after disease onset. The eGFR PRS carried no added predictive ability with regard to KF and 3P-MACE beyond established risk factors.